Do Power Consumption Data Tell the Story? - Electricity Intensity and Hidden Economy in Post-Socialist Countries - Maria Lacko (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 1999)
The paper disputes the frequently presented and quoted statement that in post-socialist economies data on power consumption are better indicators for aggregate output changes than data on official GDP. Attempt is made to show that the variation of electricity intensities in post-socialist countries does not necessarily reflect the growth of the hidden parts of the economy. Statistical and econometric analysis of data for 18 post-socialist economies show that in this region, the differences in measured and registered structural changes are more important factors explaining the differences in the changes of electricity intensity than the changing size of the unofficial economy.
Keywords: 330